Biopharmaceutical Drug Design and Development - Wu-Pong, Susanna;Ed. Rojanasakul, Yongyut;Ed (Humana Press, 1999)
This is a comprehensive survey and review of the status of the rapidly increasing array of biopharmaceuticals derived from the molecular biology approaches now so widely available.